Transtornos psiquiátricos menores e fatores associados entre travestis profissionais do sexo - Lima, Gilliard Souza (2019)
The World Health Organization (WHO) estimates that about 450 million people suffer from some psychic disorder, and one in four individuals must be affected by a psychiatric illness at some stage of his life. Between these people are sex professional transvestites whose health problems are complex due their exposition to the risk of contracting STD / AIDS, violence, depression, anxiety attacks, panic, abusive use of psychoactive substances, prejudice, besides marginalization affects quality of life and the mental health of this population segment. Although in Brazil there is a National Health Policy for Lesbian, Gay, Bisexual, Transvestite and Transsexual to be implemented in the Unified Health System, slight is the knowledgde about the Minor Psychiatric Disorders (MPD) in this population segment in the State of Mato Grosso. In this perspective, the aim was to analyze the prevalence of MPD and associated factors among sex workers. This is a cross-sectional and descriptive study. The study site was at Ponto Zero in the municipality of Várzea Grande, Mato Grosso, Brazil. A self-administered and anonymous questionnaire containing sociodemographic variables, work, psychoactive drug use pattern (ou standard), MPD and quality of life was applied. The following validated instruments were used: Self-Report Questionnaire and World Health Organization Quality of Life, in its abbreviated form. Univariate analysis of single frequency was performed, and bivariate analysis was performed using the Gross Prevalence Ratio (RPBruta), using Fisher's Exact test with the 95% confidence interval. The prevalence of MPD found was 43.7%, with emphasis on the group of psychic symptoms of depressive / anxious mood, being those most exposed to health-related behavior of transvestites aged equal to 21 years and positivity for violence (RPBruta = 1.68 IC95% 0.48-5.92), age of admission to the profession of the sex greater than 21 years (RPBruta = 1.50 IC95% 0.59-3.79), with a weekly workload of 40 hours (RPBruta = 1.43 IC95% 0.51-4.03), use in the life of tobacco (RPBruta = 1.40 IC95% 0.59- 3.29), incomplete high school ( RPBruta = 1.37 IC95% 0.53-3.52) and income lower than 4 minimum wages (RPBruta = 1.34 IC95% 0.25-7.19), but without statistical significance (p <0.05). Quality of life had shown a higher level of satisfaction in the physical and psychological domain, and the lowest level in the environmental domain. There is an elevated psychic suffering among the transvestites who had participated in this study, evidenced in the behaviors of health problems, such as drug use, violence and the conditions whom they deal with their daily work practices. The results of this research assign the necessity for more studies to identify the exposure to increase on the health problems in this population, thought to subsidize public health policies which promote more effective actions in the field of mental health, pursuing at the better quality of life of transvestites professionals.